Review of Multiaxial Testing for Very High Cycle Fatigue: From ‘Conventional’ to Ultrasonic Machines - Pedro Costa; Richard Nwawe; Henrique Soares; Luís Reis; Manuel Freitas; Yong Chen; Diogo Montalvão (Machines, 2020)
Fatigue is one of the main causes for in service failure of mechanical components and structures. With the development of new materials, such as high strength aluminium or titanium alloys with different microstructures from steels, materials no longer have a fatigue limit in the classical sense, where it was accepted that they would have ‘infinite life’ from 10 million (107) cycles. The emergence of new materials used in critical mechanical parts, including parts obtained from metal additive manufacturing (AM), the need for weight reduction and the ambition to travel greater distances in shorter periods of time, have brought many challenges to design engineers, since they demand predictability of material properties and that they are readily available. Most fatigue testing today still uses uniaxial loads. However, it is generally recognised that multiaxial stresses occur in many full-scale structures, being rare the occurrence of pure uniaxial stress states. By combining both Ultrasonic Fatigue Testing with multiaxial testing through Single-Input-Multiple-Output Modal Analysis, the high costs of both equipment and time to conduct experiments have seen a massive improvement. It is presently possible to test materials under multiaxial loading conditions and for a very high number of cycles in a fraction of the time compared to non-ultrasonic fatigue testing methods (days compared to months or years). This work presents the current status of ultrasonic fatigue testing machines working at a frequency of 20 kHz to date, with emphasis on multiaxial fatigue and very high cycle fatigue. Special attention will be put into the performance of multiaxial fatigue tests of classical cylindrical specimens under tension/torsion and flat cruciform specimens under in-plane bi-axial testing using low cost piezoelectric transducers. Together with the description of the testing machines and associated instrumentation, some experimental results of fatigue tests are presented in order to demonstrate how ultrasonic fatigue testing can be used to determine the behaviour of a steel alloy from a railway wheel at very high cycle fatigue regime when subjected to multiaxial tension/torsion loadings.